The Parity Law in Practice: Implementation and direct outcomes - Teixeira,Ana Lúcia (2021)
Abstract Portugal adopted legislative quotas in 2006, passing the so-called Parity Law which specifies that candidate lists must include a minimum representation for each sex, and neither sex can occupy more than two consecutive positions in the candidate lists. This paper follows the Gender Equality Policy in Practice (GEPP) approach and aims to deepen our understanding of the adoption and implementation process of the Parity Law in Portugal. After mapping how the law was implemented in Portugal - including a description of the tools and instruments that were set up and how the process unfolded in practice - an assessment of the policy’s direct effects is carried out, contributing to the open debate on the indicators of success related to legislative quota laws.